Diagnostic value of SPECT, PET and PET/CT in the diagnosis of coronary artery disease: A systematic review - Al Moudi, M.; Sun, Zhonghua; Lenzo, N. (University of Malaya, 2011)
Purpose: The purpose of the study was to investigate the diagnostic value of SPECT, PET and PET/CT in thediagnosis of coronary artery disease, based on a systematic review. Material and Methods: A search of PubMed/Medline and Sciencedirect databases in the English-language literature published over the last 24 years was performed. Only studies with at least 10 patients comparing SPECT, PET or combined PET/CT with invasive coronary angiography in the diagnosis of coronary artery disease (50% stenosis) were included for analysis. Sensitivities and specificities estimates pooled across studies were analysed using a Chisquare test.Results: Twenty-five studies met the selection criteria and were included for the analysis. Ten studies were performed with SPECT alone; while another six studies were performed with PET alone. Five studies were carried outwith both PET and SPECT modalities, and the remaining four studies were investigated with integrated PET-CT. Themean value of sensitivity, specificity and accuracy of these imaging modalities for the diagnosis of coronary artery disease was 82% (95%CI: 76 to 88), 76% (95%CI: 70 to 82) and 83% (95%CI: 77 to 89) for SPECT; 91% (95%CI: 85to 97), 89% (95%CI: 83 to 95) and 89% (95%CI: 83 to 95) for PET; and 85% (95%CI: 79 to 90), 83% (95%CI: 77 to 89)and 88% (95%CI: 82 to 94) for PET/CT, respectively. The diagnostic accuracy of these imaging modalities wasdependent on the radiotracers used in these studies, with ammonia resulting in the highest diagnostic value.Conclusion: Our review shows that PET has high diagnostic value for diagnosing coronary artery disease, and this indicates that it is a valuable technique for both detection and prediction of coronary artery disease.